ANALYSIS OF THE METHODS OF PREVENTION OF BURNING-IN ON THE SURFACE OF STEEL AND CAST IRON MOULDINGS - Y. Nikolaichik; F. Rudnickiy; A. Bataichuk; V. Mudryi (Литьë и металлургия, 2015)
The known theories and approaches explaining the nature of formation process of a metal penetration (burning-in) on a surface of steel and iron castings are described in the article. The methods and materials which are applied in antistick coatings and in the molding sand mixtures for prevention of defect formation is also given in the paper.